MEMBANGUN BUDAYA SEKOLAH BERLANDASKAN AJARAN AHLUSSUNNAH WAL JAMAAH - Al Darmono (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2021)
Advances in information technology have had a huge impact on human life. Through information technology, new understandings and streams influence the mindset and perspective of humans. This often leads to the failure of schools to build a harmonious culture. This study aims to determine the values ​​of the teachings of Ahlusunnah wal Jama'ah; know the importance of building a school culture based on the values ​​of tawasut, tasamuh, and tawazun. This research is a type of literature review research with a descriptive qualitative approach, data collection techniques using library documentation and data analysis techniques using content analysis (content analysis). Currently, it is very important for schools to build a culture based on the teachings of Islam Rohmatan lil alamin, a teaching that promotes peace. These teachings are actualized in the Islamic understanding of Ahlusunnah wal Jama'ah with the values ​​of tawasut, tasamuh, and tawazun. These values ​​are very relevant to be developed as a school culture to stem radical ideas that can threaten social disintegration in the school environment.